SUPERVISION OF FOREIGNERS ACCORDING TO THE IMMIGRATION LAW IN FACING POTENTIAL THREATS TO INDONESIA'S NATIONAL SECURITY - Ghozy Prananda Fakhruddin; Ale Alfero Deputra; Adhitya Antomarta (Journal of Law and Border Protection, 2022)
This paper aims to find out the national security threats that may occur with the presence of foreigners in Indonesia and the supervision of foreigners according to the immigration law in the face of potential national security threats in Indonesia. The writing of this paper uses a normative juridical approach, which is a method for studying theories, legal principles, and laws and regulations relevant to research. The data collection method used is literature study. The author conducted a literature study of laws and regulations, immigration journals, and books related to immigration. Data analysis uses qualitative normative data analysis techniques. The results of this study show that the potential security threat of Indonesia with foreigners is a form of transnational organized crime (TOC), such as Cyber Crime, Human Trafficking, terrorism, drug trafficking, and money laundering (Money Laundry). The form of immigration supervision that can be carried out due to the potential threat is administrative supervision and field supervision. In addition, to develop the advancement of science and technology, the existence of a Foreigner Reporting Application (APOA) is targeted at hotel or lodging management to provide their access waivers. APOA serves to provide reports regarding the presence of foreigners to the local immigration office. Another form of immigration supervision is the presence of the TIMPORA ForeignEr Supervision Team assigned with the aim of supervising and cracking down on foreign nationals in indonesia's administrative regions